Advances in marine biology. - Tyler, Paul A.; Southward, Alan J.; Young, Craig M. (Academic Press, 2000)
Volume 38 is a standard Advances in Marine Biology volume with two reviews: "The Enhancement of Marine Fish Stocks" and "The Biology of Pandalus." Advances in Marine Biology provides in-depth and up-to-date reviews on a variety of topics. The series also includes thematic volumes that examine a particular field in detail. Recent thematic volumes are "The Biology of Calenoid Copepods" and "Walleye Pollock."